NEW TECHNIQUES FOR SAMPLING AND CONSOLIDATION OF SEDIMENTS: APPLICATION TO BURNT SOILS FROM AN ARCHAEOLOGICAL SITE IN AUSTRIA - Aidona, E.; Scholger, R.; Mauritsch, H. J. (Bulletin of the Geological Society of Greece, 2004)
An archaeomagnetic study requires samples to be oriented very precisely prior to the removal from the site and to be transported safely since most of the times the collected samples are very soft and fragile. In this study we present new techniques for sampling and consolidation of sediments and unconsolidated soils, which are useful tools for palaeomagnetic and archaeomagnetic investigations. An application of the above techniques has been performed in burnt soils (roastbeds) in an archaeological site near Eisenerz (Austria), which used to be a cooper-smelting place in Bronze Age (around 1450 b.c.) Several roast beds have been collected and consolidated in order to investigate the distribution and the stability of the magnetization of these materials. We obtained around 350 samples and the natural remanent magnetization and the magnetic susceptibility of all these samples have been measured with a 2G squid cryogenetic magnetometer and a GEOFYSIKA KLY-2 susceptibility meter, respectively. Plots of the natural remanent magnetization and magnetic susceptibility versus depth indicate different layers of heating and give some first evidences for the use of these soils during the smelting procedure. Higher values of the intensity of the magnetization as well as of the magnetic susceptibility represent the more intense heating layer. Magnetic cleaning (thermal and Af demagnetization) of pilot samples revealed the presence of a stable component of magnetization. It seems, therefore, that these types of materials are suitable for an archaeomagnetic investigation, since they are able to record and preserve all the necessary magnetic information and provide important knowledge concerning the recent history of the Earth’s magnetic field.